Genotype GG of rs895819 Functional Polymorphism Within miR‐27a Might Increase Genetic Susceptibility to Colorectal Cancer in Han Chinese Population. Issue 4 (24th August 2015) - Jiang, Yu; Lin, Dong‐Hong; Xu, Jian‐Ping; Chen, Wen‐XU; Zheng, Shu‐Jian; Song, Lin
Abstract : Background: MicroRNA‐27a ( miR‐27a ) is supposed to be an oncogene in various types of cancers, and genetic variation of miR‐27a might result in aberrant expression and abnormal second structure of mature‐miR‐27a, contributing to elevated genetic risk and poor prognosis for colorectal cancer (CRC). Methods: In order to explore the possible association between rs895819 within miR‐27a and CRC in Han Chinese population, we investigated the genotype distributions of rs895819 in 508 CRC cases and 562 healthy check‐up controls using TaqMan genotype discrimination system, and analyzed the possible association between them. Odds ratio (OR) and 95% confidential interval (95% CI) were used to assess the strength between allele and genotype of the locus and risk of CRC. Results: In our study, we found that genotype GG of rs895819 was significantly associated with an increased risk for CRC (17.1% vs. 11.6%, adjusted OR = 1.546, 95% CI = 1.070–2.236), and allele A carrier (AA/AG) was significantly associated with a decreased risk for CRC (82.9% vs. 89.4%, adjusted OR = 0.63, 95% CI = 0.446–0.893). In addition, a significant association was observed between genotype GG and larger tumor size (>5 cm; P < 0.001), and allele G was significantly associated with higher pathological stage (TNM‐III) ( P = 0.008). Conclusion: These results indicated that miR‐27a might be involved in the development and progression of CRC, genotype GG within rs895819 might be a genetic susceptible factor for CRC. Further multicentral, large sample size, and well‐designed epidemiological study as well as functional study are warrant to verify our findings.